The Relationship of Emotional Intelligence and Commitment to Prayers with Sexual Desire in Single Students of Miyaneh City Universities - Maryam Nottaq; Qamar Kiani (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Mismanagement of emotional impulses and reduced commitment to the religious duty of prayers as well as the increased relationship between male and female students are considered as the important issues in academic environments in recent years. The present study was an attempt to investigate the relationship of emotional intelligence and commitment to prayers with sexual desire in single students of Miyaneh Universities. Methods: The statistical population included all single B.A. students in Payame Noor University and Islamic Azad University in Miyaneh, out of which a sample of 140 university students was selected using accessible sampling method. Data were collected using Petrides and Farnhaym's Emotional Intelligence Questionnaire, Panahi's Prayer Adherence Questionnaire, and Multidimensional Sexuality Questionnaire (MSQ). The data were analyzed by using Pearson correlation and multivariate regression. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: Based on the results among the components emotional intelligence, only emotion control had a negative and significant correlation with sexual desire (r=-0.236, P<0.01). In addition, commitment to prayers had a significantly negative correlation with sexual desire (r=-0.165, P<0.05). Furthermore, total emotional intelligence, emotion perception, emotion control and social skills had a positive and significant correlation with commitment to prayers (P<0.05). Optimism was not found to have a significant correlation with commitment to prayers. The capacity for predicting sexual desire by the variable of emotion control was 23 percent. Conclusion: It seems that implementing interventions to improve emotion control and commitment to prayers is effective in reducing single students' sexual desire. For downloading the full-text of this article please click here. Please cite this article as: Nottaq M, Kiani Q. The Relationship of Emotional Intelligence and Commitment to Prayers with Sexual Desire in Single Students of Miyaneh City Universities. Pizhūhish dar dīn va salāmat. 2020; 5(4): 61-72. https://doi.org/10.22037/jrrh.v5i4.21035